Prototipe Mesin CNC Diode Laser Cutting 5500 Miliwatt Untuk Pembuatan Produk Kreatif Bahan Akrilik - suharto suharto (Jurnal Poli-Teknologi, 2020)
Advances in manufacturing technology in the creative industries began to leave the dominance of the role of humans into automated systems to produce high-quality products. CNC laser machine is a computer-programmed machine used to make a product by cutting, scraping, and engraving. In general, people think that CNC machines are expensive goods. The purpose of this study was to design a prototype diode type CNC laser machine for the manufacture of creative acrylic material products. The research method uses the stages of designing, manufacturing, and testing the performance of a diode type CNC laser machine. The CNC laser machine is designed as cheaply as possible by minimizing self-made components and using standard components such as machine frames using aluminum extrusion, laser using a 5500 mWatt laser diode type, stepper motor as an X, Y, and Z axis. Control software is used by USB CNC controller . CAD software is used by Aspire Vectric and CAM software is used GRBL with Adruino Nano microprocessors. The results of a  Diode Laser CNC machine prototype with dimensions of 450×400×300 (mm); work area dimensions 300×200×35; engine weight 5 (kg). The ability to cut a diode Laser of 5.5 watt CNC machine on black acrylic 3 (mm) with an average time of 0.5 mm/s is the best result. Diode Laser CNC Machine engraving capability of clear acrylic material with dark color paper cover machining time 10 (mm / s).